2004
DOI: 10.1183/09031936.04.00005904
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis and granuloma genes: a family-based study in African-Americans

Abstract: The evidence for a genetic component in the aetiology of sarcoidosis includes familial aggregation, associations with genetic polymorphisms, and linkage to the major histocompatibility complex class region on chromosome 6p. Unfortunately, the majority of genetic associations with sarcoidosis have not been consistently replicated.In the present study, using a family-based study design, which controls for population stratification, the authors attempted to replicate previously reported associations between sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
0
35
0
2
Order By: Relevance
“…A major limitation of case-control association studies of candidate genes is that an allelic association may arise if cases and controls were drawn from genetically different populations even though no disease gene association exists. Recently, in a large family-based association study Rybicki et al 43 reported lack of associations with three candidate genes for sarcoidosis that previously had positive associations in studies that used a case control design. [44][45][46] The initial stage of a genome scan is blind to biases toward any specific group of candidate genes; however, to guard against false negatives, liberal P-values are used for follow-up of linkage signals.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of case-control association studies of candidate genes is that an allelic association may arise if cases and controls were drawn from genetically different populations even though no disease gene association exists. Recently, in a large family-based association study Rybicki et al 43 reported lack of associations with three candidate genes for sarcoidosis that previously had positive associations in studies that used a case control design. [44][45][46] The initial stage of a genome scan is blind to biases toward any specific group of candidate genes; however, to guard against false negatives, liberal P-values are used for follow-up of linkage signals.…”
Section: Discussionmentioning
confidence: 99%
“…One excluded study reported allelic frequencies; the other was family-based study (Rybicki et al 2004;Grutters et al 2002).…”
Section: Data Extractionmentioning
confidence: 99%
“…The remaining five studies not included were family-based studies, studies evaluating serum ACE levels or studies evaluating sarcoidosis symptoms (Csaszar et al 1997;Niimi et al1998;Kawakami et al 1998;Schurmann et al 2001;Rybicki et al 2004).…”
Section: Data Extractionmentioning
confidence: 99%
“…Predictably, analysis of T-cell receptor variants has also revealed patterns associated with disease susceptibility or phenotype [46]. However, poor reproducibility has characterized these studies, with substantial interpopulation variability due to population stratification, sampling error, or unsuspected differences in modifier genes/exposures between populations [2,5]. Epidemiologic observations have suggested multiple potential etiologic triggers for sarcoidosis, with the possibility that susceptibility to any putative agent may be a function of the individuals' genetic predisposition.…”
Section: Gene-environment Interactions In Sarcoidosis Evidence For Mamentioning
confidence: 99%
“…In this regard, numerous attempts to define disease susceptibility genes, usually by candidate gene approaches, although more recently using haplotype analysis, have yielded results that are poorly reproducible [5]. More recently, two whole genome scans have yielded differing results, possibly because two different populations were studied [6,7].…”
Section: Introductionmentioning
confidence: 99%